Universiti Sains Malaysia (USM) / Mohamad Hilmi Zainuddin Che Razak - Che Razak, Mohamad Hilmi Zainuddin (Perpustakaan Tengku Anis, 2019)
Industrial training an important phase of a student life. This report writing is based on industrial training which had been completed by trainee from 1 August 2018 until 31 December 2018. The trainee has undergoes 5 month of industrial training at Universiti Sains Malaysia (USM) in Pusat Pengetahuan, Komunikasi dan Teknologi (PPKT), which have four IT section that is Pejabat Timbalan Pengarah (PTP), Technical Support, Info structure and Application. Each section has its own task to manage PPKT Health Campus. The Technical Support section is headed by Encik Azahari Omar. This section divided into two sub section which is web, multimedia, e-learning manage by Encik Nareeman Shah and asset, services desk, technical support managed by Encik Azmanzaifikar Ehsan. The technical support section serves for provides technical services, procurement, distribution and management of IT equipment. In addition, it also works as managing assets, website management and multimedia. The trainee has faced multiple types of challenges and experience during the internship period where the trainee has been given a various kind of task. The trainee was given responsibilities in PPKT where the trainee requires to develop a system. The trainee has learn a lot during the internship period, which result in better improvement in lot of aspect such as discipline, skills and knowledge.